Dispersive Raman spectroscopy for the in vitro identification and quantification of injected vancomycin intra-vitreous. Issue 2 (2011) - Lora Lora, Roney Carlos Roney Carlos; Silveira Silveira, Landulfo Landulfo; Zamuner Zamuner, Stella Regina Stella Regina; Pacheco Pacheco, Marcos Tadeu Tavares Marcos Tadeu Tavares
Abstract : This work presents a study which aimed to quantify the intravitreally-injected vancomycin antibiotic using dispersive Raman spectroscopy and Partial Least Squares multivariate calibration. Eyes of New Zealand rabbits were injected with 5.0 mg vancomycin at different time intervals (8, 24 and 48 h groups). Distilled water was injected into the eyes of rabbits in the control group. The vitreous was then removed from each eyeball, placed into a quartz cuvette and submitted for dispersive Raman spectroscopy. The Raman equipment used a laser (80 mW, 830 nm), an imaging spectrograph and a CCD camera with exposure time of 50 s. A calibration curve was developed using the PLS method with vancomycin diluted in water in the range of 1.0–8.0 mg/ml. The spectrum of vancomycin was present in bands at the positions of C=C, amide I, CH3, amide III and vibrations of the carbon chain (C–C, aromatic ring breathing and C–O–C). The spectra of the injected vitreous bodies showed weak bands which were correlated with the pure drug. The PLS calibration model had a standard error of prediction of 0.8 mg/ml using one latent variable. The PLS showed changes in the predicted concentrations of the injected vitreous bodies depending on the time of injection, with an amount near zero for the water-injected group and ranging between 2 and 3 mg/ml for the drug-injected groups. Raman spectroscopy could be employed in the quantitative evaluation of intravitreally-injected vancomycin in future in vivo applications.